A new genus and species of Goniasteridae, Peedeeaster sandersoni, and the first occurrence of Sclerasterias (Asteriidae) from the Cretaceous Peedee Formation of North Carolina - Mah, Christopher L. (Zootaxa, 2022)
Two new fossil asteroids are described from the Maastrichtian (Cretaceous) Peedee Formation in North Carolina. The first, a member of the Asteriidae, is identified as Sclerasterias sp. based primarily on the superomarginals, spination, and presence of transverse ribs on the distalmost armtip. This is the first occurrence of Sclerasterias in the Cretaceous of North America. The second asteroid taxon is based on a relatively well-preserved series of specimens described as a new genus and species, Peedeeaster sandersoni (Goniasteridae) which displays a pentagonal body shape similar to those of modern Peltaster and Sphaeriodiscus and is also comparable to such Cretaceous goniasterids such as Metopaster.